Technological advancements in valorization of second generation (2G) feedstocks for bio-based succinic acid production - Narisetty, Vivek; Okibe, Maureen Chiebonam; Amulya, K.; Jokodola, Esther Oreoluwa; Coulon, Frederic; Tyagi, Vinay Kumar; Lens, Piet N. L.; Parameswaran, Binod; Kumar, Vinod (Elsevier, 2022)
Succinic acid (SA) is used as a commodity chemical and as a precursor in chemical industry to produce other derivatives such as 1,4-butaneidol, tetrahydrofuran, fumaric acid, and bio-polyesters. The production of bio-based SA from renewable feedstocks has always been in the limelight owing to the advantages of renewability, abundance and reducing climate change by CO2 capture. Considering this, the current review focuses on various 2G feedstocks such as lignocellulosic biomass, crude glycerol, and food waste for cost-effective SA production. It also highlights the importance of producing SA via separate enzymatic hydrolysis and fermentation, simultaneous saccharification and fermentation, and consolidated bioprocessing. Furthermore, recent advances in genetic engineering, and downstream SA processing are thoroughly discussed. It also elaborates on the techno-economic analysis and life cycle assessment (LCA) studies carried out to understand the economics and environmental effects of bio-based SA synthesis.
Keywords: Succinic acid; Lignocellulose; Crude glycerol; Food waste; Circular bioeconomy